Reconceptualizing Curriculum Integration and Community-Based Character Education: A Multidimensional Study of Madrasah Tarbiyah Islamiyah (MTI) Canduang - Wiana Perista; Ahmad Rivauzi (Bulletin of Community Engagement, 2025)
This study examines the managerial mechanisms employed by Madrasah Tarbiyah Islamiyah (MTI) Canduang in integrating the curriculum, implementing character education, and mobilizing Minangkabau local wisdom to respond to the disruptions of the digital age. Using a descriptive-analytical qualitative case study design, data were collected through in-depth interviews, observations, and document analysis. The results reveal four main findings. First, curriculum integration is implemented through the Shared and Nested models, where government-mandated religious subjects are integrated into the study of classical Islamic texts. Students’ cognitive load is managed through Cognitive Time Management and the Al-Miftah Lil Ulum linguistic acceleration method. Second, the character education ecosystem extends beyond the mere transfer of moral knowledge, it is enforced through a high-stakes instrument, the Character Report Card, which holds absolute veto power over academic graduation. Third, the Minangkabau epistemology, embodied in the Sumbang Duo Baleh guidelines and the Kato Nan Ampek grammar system, is directly internalized into the local curriculum by traditional leaders to strengthen the socio-cultural resilience of the students. Fourth, the institution responds to internal challenges such as the crisis of educator role models and external threats, including smartphone addiction, through a cultural compromise approach and strict digital monitoring policies, although this requires renegotiating with the permissive parenting styles of modern parents. MTI Canduang presents a blueprint for Islamic educational management that successfully harmonizes the Salaf heritage, the excellence of empirical science, and local wisdom in shaping a generation of outstanding character in the 21st century.